Smart Circular Agriculture: IoT and Zero-Waste for Digital Agriculture Implementation - Hidayati, Nanik; Ratnaningsih, Endah (LifeSciFi, 2025)
Smart Circular Agriculture links Internet of Things monitoring with zero-waste practices to improve efficiency and resilience. This study examines how the approach works in Sleman Regency and what sustains adoption. Using a qualitative explanatory sequential design, a descriptive survey mapped adoption, input efficiency, and waste handling. Follow-up interviews and field observations were then explained in terms of mechanisms, constraints, and enablers through the Miles and Huberman cycle. Findings show that moisture-triggered irrigation, app-based scheduling, and microclimate management reduced over-irrigation, stabilized nutrient dosing, and improved product uniformity. Circular routines, including residue composting, liquid organic fertilizer preparation, and simple water harvesting, lowered unmanaged organics and reduced purchased inputs. Complementarities between sensing-driven control and circular resource cycling were strongest in greenhouses, where reliability and quality premiums justified investment. Adoption reflected demographic and institutional contours; millennial farmers and enterprise-oriented producers led uptake, while diffusion depended on demonstration, maintenance, and financing. Smart Circular Agriculture is a pathway for digital transformation in Sleman. The study shows how digital feedback and circular flows co-produce agronomic benefits. Practice and policy should prioritize seasonal financing, after-sales service, integrated training, and standards for compost and liquid biofertilizer, while leveraging greenhouse clusters for scalable, sustained production.